(untitled) (Indian Journal of Case Reports, 2021)
Multisystem inflammatory syndrome in children (MISC-C), also known as the pediatric inflammatory multisystem syndrome, is a new dangerous childhood disease that may be associated with COVID disease. Signs and symptoms depend on the body part involved. We report a case of complicated post-COVID MIS-C in a 5-year-old child who presented with fever, vomiting, pain abdomen for 6 days, and rash for 2 days. Since the patient had complaints of high-grade fever for more than 5 days, rash, non-purulent conjunctivitis, cracked lips with cardiac and respiratory, and gastrointestinal involvement with positive COVID antibodies, and raised CRP; she was diagnosed to have the MIS-C post-COVID. The patient was started on oral aspirin and oral prednisolone for 2 weeks and discharged with proper advice.